AN ANALYSIS OF FIGURATIVE LANGUAGE IN A THOUSAND YEARS SONG LYRICS BY CRISTINA PERRI - Astriani, Ai Siti; Bhuana, Gartika Pandu (PROJECT (Professional Journal of English Education), 2021)
The tittle of this research is â€œAn Analysis of Figurative Language in A Thousand Years Song Lyrics By Cristina Perriâ€. The purpose of this research is to know the types of figurative language and the contextual meanings of figurative language used in â€œA Thousand Yearsâ€ song. The method was descriptive quatilative research. The song lyrics took from lyricfind.com. The results showed that there were five figurative languages in that song: rhetoric, hyperbole, paradox, repetition, and personification. Hyperbole and repetition were the dominant form used. Both forms were dominantly used to convince and emphasize that the woman was really waiting for the man and her love was very sincere to him. Thus, he did not need to doubt her love because she loved him before and would continue to love him for a long time.Â Â Â Keywords:Â  Figurative Language, Types of Figurative Language, Song Lyrics